Clinical Assessment of the Safety and Effectiveness of Nonablative Fractional Laser Combined with Transdermal Delivery of Botulinum Toxin A in Treating Periocular Wrinkles. Issue 8 (August 2016) - Fan, Xing; Yin, Yue; Wang, Shiping; Li, Tong; Xue, Ping; Yang, Qing; Ma, Qiaoxin
Abstract : Summary: The upper and lower eyelids are traditionally contraindicated for subcutaneous botulinum toxin A (BTX) injection because of possible complications. We assessed the clinical safety and effectiveness of nonablative fractional laser (NAFL) combined with transdermal delivery of BTX in the treatment of periocular wrinkles. Thirty patients who had periocular wrinkles were treated with 1, 565-nm NAFL in combination in the left periocular area and normal saline in the corresponding area of the right eye. VISIA skin detector was used to photograph and compare the changes induced by treatment. We also recorded the comfort level of the patients. All 28 patients could tolerate the pain caused by the laser treatment and showed no apparent discomfort during percutaneous drug delivery. No chromatosis or ptosis of upper eyelids occurred after the treatment. We used VISIA to detect changes at 1 week, 1 month, 3 months, and 6 months, respectively, after the treatment. The periocular wrinkles decreased, and the flabbiness of eyelids was significantly reduced. The upper and lower eyelids are traditionally contraindicated for subcutaneous BTX injection, as it may cause complications. The treatment combining 1, 565-nm NAFL and transdermal delivery of BTX can decrease periocular wrinkles and flabbiness while avoiding complications to the greatest extent. None of the 28 patients who had completed the treatment suffered from complications or adverse effects; all were satisfied with the treatment outcome.